let the equation of function is
y = mx + c
so it will satisfy all the points of the table.
(-8, 3)
3 = m(-8) + c
-8m +c = 3 ....(1)
for (-16, 20)
20 = m(-16)+ c
-16m +c = 20 ......(2)
subtract both the equation
-16m -(-8m) + c - c = 20 - 3
-8m + 0 = 17
m = -17/8
now, multiplied equation 1 by 2
-16m + 2c = 6
- 16m + c = 20
subtract the equation,
-16m -(-16m) + c - 2c = 20 - 6
0 - c = 14
c = -14
so the equation is,
y = (-17/8) x - 14
put y = -16
- 16 = (-17/8)x - 14
-16 + 14 = -17/8x
-2 = -17/8x
x = 16/17